RENÉ GIRARDS ABSOLUTE THEORIE - Vergote, Antoine (Tijdschrift voor filosofie, 1996)
The author deals with Girard's major theoretical works, not his literary analyses. Girard pretends to propose 'an absolute theory', which would explain the origin of religion, gods, rituals, ethical laws, schizophrenia, wars, etc. The epistemological statute of this 'theory' seems difficult to identify: it is not philosophy, not clinical anthropology, perhaps a kind of cultural anthropology. An absolute theory of course cannot be verified; but it may be falsified. Author then examines the basic concept: that of mimetic desire leading to violence. It seems essential to introduce (clinically and anthropologically) four modalities of mimetic desire, involving four kinds of possible violence. Girard, however, identifies mimetic desire with just one type, notably the paranoid one, the one which necessarily leads to violence. Author further examines the 'absolute theory' built on the basic conept. Girard posits as starting point of religion, ethics, etc., the 'scapegoat'. But he confuses the sociological metaphor with the religious ritual. He then asserts that the religious rite, especially the sacrificial one, is the hidden repetition of the scapegoat and only results in sour victory over violence. Actually the symbolism and the intention of both religious rituals are quite opposite. Girard therefore should take into account his own statement in The Scapegoat: ?If you try to prove too hard something, you prove nothing?.